Sistem Informasi Penjualan Buku Berbasis Web Pada Toko Buku Nasyrul Ilmi Medan - Gabriella Yolanda Hutabarat; Rena Nainggolan; Rijois I. E. Saragih (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
The trade system can be impacted directly or indirectly by today's rapid technological advancement. We currently only have access to e-commerce via the Internet, which allows us to select the items we want, learn more about them, and conduct business with anyone, regardless of distance or time. If Nasyrul Ilmi bookstore wants to improve the quality and efficiency of its book sales services, it needs to implement information technology. In this context, the author creates a sales information system that is hosted on a website in order to improve the store's operations and broaden its market reach. The goal of this study is to create a bookstore-specific sales information system that is both efficient and useful. Through needs investigation, natural UI configuration, organized data set advancement, and site-based framework execution, these objectives can be accomplished. Customers can buy books online via the store's website thanks to the sales information system. It also helps the store owner manage inventory, process orders, analyze sales, and track shipments. It is anticipated that Nasyrul Ilmi Bookstore will be able to enhance customer service quality, increase market reach, and increase operational efficiency by implementing this system. In addition, the store has a competitive advantage thanks to this system in the digital era's increasingly competitive book sales market.